2006
DOI: 10.1177/1066480705285731
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Counselors-in-Training to Work With Couples: Using Role-Plays and Reflecting Teams

Abstract: The use of experiential learning practices is a cornerstone of marriage and family training. In this article, two novel experiential approaches for teaching couples counseling are detailed. Specifically, the evolution from the original format to the final version of the learning experience is described. The two primary components of the experiences include (a) a semester-long role-play enacted by doctoral student graduate assistants and (b) student reflecting teams. The authors found that students benefited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, authors have identified potential obstacles counseloreducators may experience when deciding to implement a specific educational strategy involving role-play and technology. For example, although role-playing has been discussed as beneficial for students in many areas in the counselor training curriculum (Burnett, Hamel, & Long, 2004;Shurts et al, 2006;Stockton & Toth, 1996;Young, 2008), a limited number of specific suggestions or guidelines exist as to how counselor-educators might use this approach with counselor trainees (Smith, 2009). Furthermore, counselor-educators who would like to consider incorporating multimedia strategies such as digital video recording into their teaching may feel less than competent and perhaps even intimidated in terms of dealing with emerging technology that may be perceived as complicated (Glass, Daniel, Mason, & Parks-Savage, 2005).…”
mentioning
confidence: 99%
“…However, authors have identified potential obstacles counseloreducators may experience when deciding to implement a specific educational strategy involving role-play and technology. For example, although role-playing has been discussed as beneficial for students in many areas in the counselor training curriculum (Burnett, Hamel, & Long, 2004;Shurts et al, 2006;Stockton & Toth, 1996;Young, 2008), a limited number of specific suggestions or guidelines exist as to how counselor-educators might use this approach with counselor trainees (Smith, 2009). Furthermore, counselor-educators who would like to consider incorporating multimedia strategies such as digital video recording into their teaching may feel less than competent and perhaps even intimidated in terms of dealing with emerging technology that may be perceived as complicated (Glass, Daniel, Mason, & Parks-Savage, 2005).…”
mentioning
confidence: 99%
“…40 Thus, experiential classroom activities are critical to learning counseling microskills. [40][41][42] We use a variety of experiential learning activities, such as role-play activities, simulated patients, video tape recording, and real-life patients, in our clinical courses to both maximize our students' skill development and best evaluate student progress. We recommend that audiology instructors utilize these methods to teach and evaluate counseling microskills.…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Best teaching practices in psychology and counseling support the use of role-plays and experiential learning activities in the classroom. [40][41][42] These are effective ways to use classroom time in a productive manner that facilitates skill development and refinement. However, learning and evaluating microskills should not be limited to peer role-plays.…”
Section: Students May Initially Feel More Comfortablementioning
confidence: 99%
“…In focusing on the learning process, counselor educators can emphasize activities occurring throughout the game (i.e., role-playing scenarios), instead of emphasizing the goal of winning the game. Shurts et al (2006) reported that students expressed that the integration of role-plays within a couples counseling course contributed to their development as counselors. Roleplaying may occur without integrating it within a game; however, the context of a game (e.g., collaboration and enjoyment) may enhance the learning experience.…”
Section: Experiential-learning Theorymentioning
confidence: 98%